Asymmetric structure color generator device and preparation method and application thereof
By adopting asymmetric structure color generator devices in hydrovoltaic power generation devices, and using the combination of hygroscopic dry gel layer and asymmetric structure color layer, the problems of low power generation efficiency and poor stability of existing hydrovoltaic power generation devices are solved, and efficient and long-term power output is achieved.
Patent Information
- Application Number
- CN202411610898.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-04
AI Technical Summary
Existing hydrovoltaic power generation devices have problems such as low power generation efficiency, long response time, and poor power generation stability. It is necessary to improve the power generation performance of hydrovoltaic power generation devices.
Asymmetrical structure color generator device is adopted, including a hygroscopic dry gel layer and an asymmetrical structure color layer bonded to the hygroscopic dry gel layer. The asymmetry between the active layer of the black conductive material and the colored structure color layer forms a difference in evaporation rate under sunlight, and combines photothermal evaporation driving technology and electrochemical asymmetric technology to generate electricity together.
It realizes efficient and stable power output, high voltage output (up to 0.75V), long power generation duration (>100h), and has spontaneous hygroscopic cycling and high toughness.
Smart Images

Figure CN119561415A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrovoltaic power generation, and in particular to an asymmetric structural color generator device and a preparation method and application thereof. Background Art
[0002] With the growing demand for energy and increasing attention to environmental protection, it is imperative to find sustainable clean energy. As one of the most abundant resources on earth, the energy contained in water has not been fully utilized, so hydroelectric power generation has gradually emerged.
[0003] Unlike traditional hydropower generation that utilizes large-scale water flow, hydrovoltaic power generation focuses on the interaction between water and materials at the microscopic level. However, current hydrovoltaic power generation devices have certain defects, such as low power generation efficiency, long response time, and poor power generation stability.
[0004] Therefore, it is necessary to provide a technical solution to improve the power generation performance of hydrovoltaic power generation devices. Summary of the invention
[0005] In view of this, the present application provides an asymmetric structural color generator device and a preparation method and application thereof, which are used to solve the problem of how to improve the power generation performance of hydrovoltaic power generation devices.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In the first aspect, the present application provides an asymmetric structural color generator device, comprising a hygroscopic dry gel layer and an asymmetric structural color layer bonded to the hygroscopic dry gel layer; the asymmetric structural color layer comprises a black conductive material active layer and a colored structural color layer partially covering the surface of the black conductive material active layer; the hygroscopic dry gel layer is bonded to the black conductive material active layer.
[0007] Preferably, the area of the colored structural color layer is 1 / 3-2 / 3 of the area of the black conductive material active layer.
[0008] Preferably, the black conductive material active layer is a fabric layer containing polypyrrole.
[0009] In a second aspect, the present application provides a method for preparing an asymmetric structural color generator device, comprising the following steps: S1. dispersing the gel material, the conductive material, the hygroscopic material, the initiator, and the cross-linking agent into water, heating the reaction, and then freeze-drying to obtain a hygroscopic dry gel layer; S2. The fabric is immersed in a pyrrole mixture containing a dopant, and then a ferric chloride solution is added to perform a polymerization reaction to obtain an active layer of a black conductive material; S3. Using DA-Tris solution and polyvinyl pyrrolidone solution, a colored structural color layer is attached to one side of a portion of the black conductive material active layer to obtain an asymmetric structural color layer; S4. Bonding the side of the asymmetric structural color layer to which the colored structural color layer is not attached to the hygroscopic dry gel layer by means of an adhesive to obtain an asymmetric structural color generator device.
[0010] Preferably, in step S1, the gel material includes one or more of chitosan, polyacrylic acid, polyethylene glycol, and polyacrylamide; the conductive material includes one or more of pyrrole, carbon nanopowder, graphene, carbon nanotubes, Mxene, and nanocarbon black; the hygroscopic material includes lithium chloride; the initiator includes one or more of potassium persulfate, hydrogen peroxide, and tert-butyl hydroperoxide; and the cross-linking agent includes NN dimethyl acrylamide.
[0011] Preferably, in step S1, the heating reaction temperature is 65-75°C and the time is 1.5-3h.
[0012] Preferably, in step S2, the pyrrole mixture containing a dopant includes a mixture of a surfactant, an organic protonic acid, and pyrrole; the fabric includes one or more of silk fabric, cotton fabric, and linen fabric; the polymerization reaction temperature is 0-5°C, and the reaction time is 2-4h.
[0013] Preferably, the specific operation of step S3 is: immersing the active layer of the black conductive material partially in the DA-Tris solution, allowing it to stand to form a colored structural color film, then adding polyvinyl pyrrolidone to terminate the reaction, and removing the unreacted DA-Tris solution to allow the colored structural color film to settle and attach unilaterally to the surface of the immersed black conductive material active layer, thereby obtaining an asymmetric structural color layer.
[0014] Preferably, in step S3, the DA-Tris solution includes 10-20 mmol / L dopamine hydrochloride, 20-30 mmol / L tromethamine, 2-5 mmol / L copper chloride, and 25-35 mmol / L hydrogen peroxide, and the pH value of the DA-Tris solution is 8.5-9; and the standing time is 6-24 h.
[0015] In a third aspect, the present application provides an application of an asymmetric structural color generator device in the field of hydrovoltaic power generation.
[0016] The beneficial effects of this application are as follows: The asymmetric structural color power generator device prepared in the present application has spontaneous moisture absorption and circulation, and can combine photothermal evaporation driving technology and electrochemical asymmetric technology to synergistically generate electricity. The black conductive material active layer on the asymmetric structural color layer forms an electrochemical with the colored structural color layer, and the generated electrical energy output is high. No additional energy output is required. The power generation method is highly spontaneous, less restricted by the environment, and has high energy output.
[0017] The asymmetric structural color generator device of the present application can provide stable humidity conditions for the surface fabric due to the hygroscopic effect of the hygroscopic dry gel layer. It does not need to rely on dripping liquid to maintain voltage output and can generate electricity stably for a long time. The color of the asymmetric structural color layer is bright and adjustable, and the power generation effect presented by different colors can be controlled. At the same time, the hygroscopic dry gel layer has ultra-high toughness.
[0018] The asymmetric structural color generator device of the present application has a fast response speed, a high voltage output (up to 0.75V), and a long power generation duration (>100h). BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic diagram of a generator device according to Embodiment 1 of the present invention; Figure 1 Among them, 1. Hygroscopic dry gel layer; 2. Black conductive material active layer; 3. Colored structural color layer; Figure 2 The Vt diagram of the generator device of Examples 1-3 of the present invention measured at the same temperature and humidity; Figure 3 It is a temperature curve diagram of the generator device of Examples 1-3 of the present invention measured at the same humidity; Figure 4 Absorption spectra of the power generator device of Examples 1-3 of the present invention; Figure 5 This is a moisture absorption cycle data diagram of the generator device of Example 1 of the present invention; Figure 6 The Vt graph of the power generator device of Example 1 of the present invention and the power generator device of Comparative Example 3 measured at the same temperature and humidity; Figure 7 This is a diagram showing the tensile properties of the power generator device according to Example 1 of the present invention. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0021] Definition of terms Colored structural color: color that can reflect light of a specific wavelength, referring to other colors excluding black.
[0022] The present application provides an asymmetric structural color generator device, comprising a hygroscopic dry gel layer and an asymmetric structural color layer bonded to the hygroscopic dry gel layer; the asymmetric structural color layer comprises a black conductive material active layer and a colored structural color layer partially covering the surface of the black conductive material active layer; the hygroscopic dry gel layer is bonded to the black conductive material active layer.
[0023] In the present application, colored structural colors are colors with different absorbances from black in the wavelength range of 0.5μm to 2.5μm, including but not limited to red, yellow, green, and blue. The "asymmetric" in the asymmetric structural color layer means that the color of the structural color layer and the black conductive material active layer are different, as well as the electrochemical properties are different. The asymmetric structural color generator device of the present application has spontaneous moisture absorption cycle, good power generation performance and good toughness.
[0024] The asymmetric structural color generator device prepared in this application has spontaneous moisture absorption and circulation, and can combine the two technologies of photothermal evaporation drive technology and electrochemical asymmetric technology to generate electricity synergistically. The principle is that the asymmetric structure of the color of the black conductive material active layer and the colored structural color layer partially covering the surface of the black conductive material active layer forms a difference in evaporation rate under sunlight, so that a difference in humidity is formed at both ends of the asymmetric structural color layer to generate electricity. At the same time, the black conductive material active layer on the asymmetric structural color layer and the colored structural color layer form an electrochemical asymmetry and also form a power generation effect. The generated electrical energy output is high, no additional energy output is required, the power generation method is highly spontaneous, less restricted by the environment, and has high energy output.
[0025] The asymmetric structural color generator device of the present application can provide stable humidity conditions for the surface fabric due to the hygroscopic effect of the hygroscopic dry gel layer. It does not need to rely on dripping liquid to maintain voltage output to generate electricity stably for a long time. The color of the asymmetric structural color layer is bright and adjustable, and the power generation effect presented by different colors is controllable. At the same time, the hygroscopic dry gel layer has ultra-high toughness. The present invention can be applied to a variety of application scenarios.
[0026] The asymmetric structural color generator device of the present application has a fast response speed, a high voltage output (up to 0.75V), and a long power generation duration (>100h).
[0027] In some embodiments, the area of the colored structural color layer is 1 / 3-2 / 3 of the area of the black conductive material active layer.
[0028] In some embodiments, the black conductive material active layer is a fabric layer comprising polypyrrole.
[0029] In the present application, black and conductive polypyrrole is embedded and / or covered in the fabric to form a polypyrrole / fabric composite as a whole, the width of the fabric is the same as the width of the hygroscopic dry gel layer, the length of the fabric is 2-4 cm longer than the length of the hygroscopic dry gel layer, and the thickness of the hygroscopic dry gel layer is 1-2 mm.
[0030] The present application provides a method for preparing an asymmetric structural color generator device, comprising the following steps: S1. dispersing the gel material, the conductive material, the hygroscopic material, the initiator, and the cross-linking agent into water, heating the reaction, and then freeze-drying to obtain a hygroscopic dry gel layer; S2. Immersing the fabric in a pyrrole mixture containing a dopant, and then adding a ferric chloride solution to perform a polymerization reaction to obtain an active layer of a black conductive material; step S2 also includes a pretreatment step of first placing the fabric in an organic solvent and deionized water for ultrasonic cleaning, and then taking it out for drying. After the polymerization reaction is completed, the fabric is taken out, washed with deionized water and an organic solvent in sequence to remove excess reagents, and vacuum dried at 50-60° C. to constant weight; the organic solvent is one or more of anhydrous ethanol, methanol, and propanol; S3. Using DA-Tris solution and polyvinyl pyrrolidone solution, a colored structural color layer is attached to one side of a portion of the black conductive material active layer to obtain an asymmetric structural color layer; S4. Bonding the side of the asymmetric structural color layer to which the colored structural color layer is not attached to the hygroscopic dry gel layer by means of an adhesive to obtain an asymmetric structural color generator device.
[0031] In some embodiments, the concentration of ferric chloride is 0.5-1 mol, and the dosage is 100-200 ml.
[0032] In the present application, anhydrous ferric chloride is introduced when preparing the active layer of black conductive material. On the one hand, anhydrous ferric chloride acts as an oxidant. In the preparation step, when anhydrous ferric chloride contacts a pyrrole (Py) mixture containing a dopant, a polymerization reaction is triggered. Anhydrous ferric chloride promotes the oxidative polymerization of pyrrole monomers, and the polymerization reaction is conducive to forming the structure of a conductive cotton fabric, because it helps to form a uniform black conductive material coating on the fabric, that is, a black conductive material active layer. Since the polymerization product polypyrrole is conductive, it is conducive to application in electronic equipment, sensors, electromagnetic shielding and other fields. On the other hand, in some embodiments, the fabric is a cotton fabric, and the iron ions produced by anhydrous ferric chloride in the reaction can react with the hydroxyl groups on the cotton fabric to form a stable complex, which helps to improve the adhesion between the conductive layer and the cotton fabric substrate, thereby improving the durability, stability and toughness of the final product. Therefore, anhydrous ferric chloride not only promotes the formation of the black conductive polymer polypyrrole as an oxidant, but also helps to enhance the bonding force between the conductive layer and the cotton fabric.
[0033] In some embodiments, in step S1, the gel material includes one or more of chitosan, polyacrylic acid, polyethylene glycol, and polyacrylamide, and the concentration of the gel material is 0.01-0.015 mg / ml; the conductive material includes one or more of pyrrole, carbon nanopowder, graphene, carbon nanotubes, Mxene, and nanocarbon black; the hygroscopic material includes lithium chloride; the initiator includes one or more of potassium persulfate, hydrogen peroxide, and tert-butyl hydroperoxide; and the cross-linking agent includes NN dimethyl acrylamide.
[0034] The conductive material of the present application enables the hygroscopic dry gel layer to have not only good mechanical properties but also certain electrical conductivity; the gel material of the present application improves the mechanical strength of the hygroscopic dry gel layer. The present application introduces hygroscopic materials, including but not limited to lithium chloride, to improve the hygroscopicity of the hygroscopic dry gel layer and at the same time improve the stability of the gel. The hygroscopic dry gel layer after freeze-drying can spontaneously absorb water molecules in the surrounding environment and regenerate itself to its original state. This characteristic enables the hygroscopic dry gel layer to have a wider operating temperature range and a longer service life, and also greatly improves the efficiency of moisture power generation.
[0035] In some embodiments, step S1 is to dissolve chitosan in an acidic solution by stirring at a speed of 8000-10000 r·min-1, and at the same time add a hygroscopic material, and then add a conductive material, an initiator, and a cross-linking agent, heat the reaction to polymerize, and then put it into a -16°C ultra-low temperature refrigerator to freeze it into ice crystals, and then freeze-dry it in a -56°C freeze dryer to obtain a hygroscopic dry gel layer. The acidic solution is one or more of acrylic acid, acetic acid, lactic acid, and formic acid.
[0036] In some embodiments, in step S1, the heating reaction temperature is 65-75°C and the time is 1.5-3h.
[0037] In some embodiments, in step S2, the pyrrole mixture containing a dopant includes a mixture of a surfactant, an organic protonic acid, and pyrrole; the fabric includes one or more of silk fabric, cotton fabric, and linen fabric, preferably, the fabric is cotton fabric; the polymerization reaction temperature is 0-5°C, and the time is 2-4h.
[0038] In some embodiments, the dopant includes an organic protonic acid; the pyrrole mixture containing the dopant is a mixture of 0.1-0.2 mol pyrrole, 0.002-0.004 mol hexadecyltrimethylammonium bromide, 0.002-0.004 mol sodium dodecylbenzenesulfonate and 0.1-0.2 mol p-toluenesulfonic acid. In step S2, the amount of the pyrrole mixture containing the dopant is 100-200 ml.
[0039] In the present application, pyrrole can form a polymer with good conductive properties, namely polypyrrole (PPy), under the action of a dopant, and the conductivity of pyrrole itself is better than that of the CNT solution in the prior art. The dopant includes an organic protonic acid to increase the conductivity of polypyrrole while maintaining stability. Therefore, the pyrrole mixture containing a dopant in the present application has high conductivity and stability, which is beneficial for more effectively converting absorbed moisture into electrical energy in wet gas power generation applications. When the asymmetric structural color generator device comes into contact with moisture, polypyrrole can respond quickly and generate current, thereby achieving efficient wet gas power generation. The asymmetric structural color generator device of the present application has a fast response speed, a high voltage output (0.75V), and a long power generation duration (>100h).
[0040] In some embodiments, the specific operation of step S3 is: partially immersing the active layer of the black conductive material in a DA-Tris solution, allowing it to stand to form a colored structural color film, then injecting polyvinyl pyrrolidone into the DA-Tris solution to terminate the reaction, and removing the unreacted DA-Tris solution to allow the colored structural color film to settle and attach unilaterally to the surface of the immersed black conductive material active layer, taking it out and drying it, the drying temperature is 30-50°C, and the drying time is 3-6h, so as to obtain an asymmetric structural color layer; the concentration of the polyvinyl pyrrolidone solution is 6-25mg / mL, preferably 6-10mg / mL; preferably, the polyvinyl pyrrolidone is PVP-K30.
[0041] In some embodiments, in step S3, the DA-Tris solution includes 10-20 mmol / L dopamine hydrochloride, 20-30 mmol / L tromethamine, 2-5 mmol / L copper chloride, and 25-35 mmol / L hydrogen peroxide, and the pH value of the DA-Tris solution is 8.5-9; and the standing time is 6-24 h.
[0042] In some embodiments, the binder in step S4 includes a polyvinyl alcohol aqueous solution, and the concentration of the polyvinyl alcohol aqueous solution is 3-15 mg / ml, preferably 5-10 mg / ml.
[0043] The present application provides an application of an asymmetric structural color generator device in the field of hydrovoltaic power generation.
[0044] The present solution is further described below through specific embodiments.
[0045] Source of raw materials In the following examples, the textiles used were from Wuhan Gaoqiang Textile Factory, the drugs used were from Sinopharm Group Co., Ltd., and the conductive materials used were from Nanjing Xianfeng Nanomaterials Technology Co., Ltd.
[0046] The preparation method of DA-Tris mixed solution is as follows: take two clean beakers, in the first beaker, take 0.12g dopamine hydrochloride and add 20mL deionized water to prepare DA (dopamine hydrochloride) solution, in the second beaker, take 0.12g tromethamine, 0.017g CuCl2, 0.135g 30wt% H2O2 and add 20mL deionized water to prepare pH=8.5 Tris buffer solution, stir the solutions in the two beakers at a rate of 500r·min-1 for 15min, then mix the solutions in the two beakers, continue stirring for 5min, and obtain DA-Tris mixed solution. Prepare and use immediately.
[0047] Pyrrole mixture containing dopant: 0.79 g pyrrole, 0.0728 g hexadecyltrimethylammonium bromide, 0.0544 g sodium dodecylbenzenesulfonate and 0.98 g p-toluenesulfonic acid, 100 ml deionized water were taken and stirred for 30 min.
[0048] PVA solution: Take 1g of polyvinyl alcohol (PVA1750±50) and add it into 100mL of deionized water and dissolve it evenly to obtain a 1w / v% PVA solution.
[0049] Example 1 A method for preparing an asymmetric structural color generator device comprises the following steps: S1. 0.2g of nano carbon black, 0.4g of chitosan, 6g of acrylic acid, 24ml of water, 2g of lithium chloride, 0.3g of ammonium persulfate, and 0.01g of N-N-dimethyl acrylamide were stirred at 70°C, the dispersion was poured into a mold, and placed in a refrigerator for 24h pre-freezing treatment at a pre-freezing temperature of -16°C. The frozen sample was taken out and placed in a freeze dryer for 24h vacuum freeze drying treatment at a freeze dryer operating condition of -56°C and 2MPa. The sample was then taken out and cut into small pieces of 3cm×6cm in size and 4mm in thickness to obtain a hygroscopic dry gel layer; S2. Cut a 3cm×8cm cotton strip, put it into anhydrous ethanol and deionized water for ultrasonic cleaning for 15 minutes, then take it out and put it into an oven to dry at 30°C for 3 hours, and put it into the pyrrole mixture containing the dopant. At the same time, take 8.1g of ferric chloride and dissolve it in 100ml of deionized water. The mixed ferric chloride solution is slowly added to the pyrrole mixture containing the dopant at a rate of 1 drop per second, and polymerized at 0°C for 2 hours. Then take out the cotton strip and put it into an oven to dry at 50°C for 6 hours to obtain a black conductive material active layer; S3. Place the culture dish in a 30℃ constant temperature oven, pour the newly prepared DA-Tris mixed solution into it, soak the 1 / 2 size of the pretreated cotton strip (black conductive material active layer) in the DA-Tris mixed solution obliquely, wait for 22 hours to obtain a bright purple structural color cotton strip, then use a 10mL needle syringe to absorb 10mL of 10mg / mL polyvinyl pyrrolidone (PVP-K30) solution, and slowly inject it into the DA-Tris mixed solution along the side wall of the culture dish (to terminate the reaction) to prevent the structural color film from being broken. After 30 minutes, use a needle syringe to absorb the unreacted DA-Tris mixed solution at the bottom layer to allow the colored structural color film to settle and attach to the surface of the soaked black conductive material active layer on one side. Then take out the structural color cotton strip and put it in an oven to dry. The oven temperature is 30℃ and the time is 3h to obtain an asymmetric structural color layer. S4. Place the side of the asymmetric structural color layer that has not formed a colored structural color film upward on the table, take 5mL of 1w / v% PVA solution and evenly add it to the cotton strip (the side that has not formed an asymmetric structural color), then place the hygroscopic dry gel layer flat on the cotton strip and let it stand for 6 hours to obtain an asymmetric structural color generator device, recorded as a "purple-gel" generator.
[0050] Example 2 A method for preparing an asymmetric structural color generator device, the other contents are the same as those of Example 1, except that in step S3, 1 / 2 the size of the pretreated cotton cloth strip (black conductive material active layer) is immersed obliquely in a DA-Tris mixed solution and waited for 6 hours to obtain an asymmetric structural color generator device, which is recorded as a "blue-gel" generator.
[0051] Example 3 A method for preparing an asymmetric structural color generator device, the other contents are the same as those of Example 1, except that in step S3, 1 / 2 the size of the pretreated cotton cloth strip (black conductive material active layer) is immersed obliquely in a DA-Tris mixed solution and waited for 24 hours to obtain an asymmetric structural color generator device, which is recorded as a "green-gel" generator.
[0052] Comparative Example 1 A method for preparing an asymmetric structural color generator device, the other contents are the same as those in Example 1, except that the pretreated cotton cloth strips (black conductive material active layer) are all immersed in a DA-Tris mixed solution and wait for 22 hours to obtain a structural color generator device, which is recorded as an "all purple-gel" generator.
[0053] Comparative Example 2 A method for preparing a generator device, the other contents of which are the same as those of Example 1, except that step S3 is not included, and a generator device is obtained, which is recorded as a "polypyrrole-gel" generator.
[0054] Comparative Example 3 A method for preparing an asymmetric structural color generator device, the other contents are the same as those of Example 1, except that steps S1 and S4 are not included, and a "polypyrrole-purple cotton fabric" generator is obtained.
[0055] Comparative Example 4 A method for preparing an asymmetric structural color generator device, the other contents are the same as those of Example 1, except that the method does not include adding a ferric chloride solution.
[0056] Comparative Example 5 A method for preparing an asymmetric structural color generator device, the other contents are the same as those of Example 1, except that the pyrrole mixture containing a dopant does not include the dopant (sodium dodecylbenzenesulfonate and p-toluenesulfonic acid).
[0057] Test and Evaluation The generators obtained in each embodiment and comparative example were subjected to performance tests, including the following contents: (1) Voltage change test: Measured by electrochemical workstation (CHI660E). Connect the positive and negative electrodes to the two ends of the cotton fabric in the generator device, and start recording data after the voltage stabilizes after 1 minute. When measuring the voltage, the ambient temperature is 30~40℃ and the relative humidity is 56~62%.
[0058] (2) Tensile property test: The dry gel was made into a sample with a length of 4 cm, a width of 1 cm, and a thickness of 0.4 mm. The chuck sensitivity was 500 N, the test rate was 15 mm min-1, the clamping distance was set to 2 cm, and the average force value was 20 N.
[0059] (2) Thermocouple test: K-type thermocouple sensors were placed at the bottom of the asymmetric structural color fabric to test the temperature of the sandwich structure generator. A two-channel temperature recorder (TA612C) was used to record the real-time temperature. A xenon lamp (CELHXF300, Education Au-light) was used to simulate sunlight 30 cm above the generator device. The xenon lamp irradiated the surface of the structural color fabric vertically with a light intensity of 1 kW / m2. In order to shield the influence of heat convection, a polyethylene film was covered above the sandwich structure generator device. The relative humidity of the environment was 56 ~ 62% when measuring the temperature.
[0060] (3) Solar radiation absorption test: The sample was scanned for 2 min using an integrating sphere UV-visible spectrophotometer (UV-3600plus) with a scanning step of 2 nm.
[0061] (4) Water loss cycle test: The generator was placed in a petri dish and then left in the air. After 2 hours, the generator was completely wetted and then placed on an electronic balance. In order to shield the photothermal evaporation of the water surface, a groove slightly larger than the generator was cut out on the tin foil and the generator was placed in it. At the same time, a cylindrical glass cover (24 cm in diameter and 10 cm in height) was placed above the petri dish. The simulated sunlight 15 cm above the glass cover was provided by a xenon lamp (CELHXF300, Education Au-light), which irradiated the surface of the generator vertically with a light intensity of 1 kW / m2. An electronic balance (Sartorius, SQP, QUINTIX224-1CN) was used to monitor the mass change of the generator over time. The ambient temperature during the evaporation test was 50~55℃ and the time was 6h.
[0062] (5) Tensile strength test: The dry gel was made into a sample with a length of 4 cm, a width of 2 cm, and a thickness of 4 cm. The chuck sensitivity was 500 N, the test speed was 15 mm·min-1, the clamping distance was set to 2 cm, and the average force value was 15 N.
[0063] The above test results are as follows: Figure 2 The Vt graph of a hydrovoltaic super-tough asymmetric structural color generator device with spontaneous moisture absorption cycle prepared in Examples 1-3 of the present invention measured at the same temperature and humidity. It can be seen that the sandwich structure generator device ("purple-gel" generator) prepared in Example 1 has a higher voltage output than the "green-gel" generator in Example 2 and the "blue-gel" generator in Example 3.
[0064] Figure 3 The temperature curve of a hydrovoltaic super-tough asymmetric structural color generator device with spontaneous moisture absorption cycle prepared in Examples 1-3 of the present invention measured at the same humidity. It can be seen that the asymmetric structural colors (black and purple) in the sandwich structure generator device ("purple-gel" generator) prepared in Example 1 have a larger temperature difference than other asymmetric structural colors (black and blue) and asymmetric structural colors (black and green), and the asymmetric effect of photothermal evaporation is better.
[0065] Figure 4This is an absorption spectrum of a hydrovoltaic super-tough asymmetric structural color generator device with spontaneous moisture absorption cycle prepared in Example 1-3 of the present invention. It can be seen that the polypyrrole coating in the asymmetric structural color has an absorbance of nearly 90% in the wavelength range of 0.5μm~2.5μm, and different color structural colors in the asymmetric structural color have different absorbances in the wavelength range of 0.5μm~2.5μm (absorbance size: black>green>blue>purple), which proves that the hydrovoltaic sandwich structure generator device based on asymmetric structural color prepared by the present invention can be applied to a variety of different scenarios and has a wide range of applications.
[0066] Figure 5 This is a moisture absorption cycle data diagram of a hydrovoltaic super-tough asymmetric structural color generator device with spontaneous moisture absorption cycle prepared in Example 1 of the present invention. It can be seen that the "purple-gel" generator can maintain a constant moisture absorption effect after multiple dry-wet cycles due to the self-hygroscopic effect of the gel, which is conducive to continuous and stable power generation.
[0067] Figure 6 The Vt graphs of a hydrovoltaic super-tough asymmetric structural color generator device ("purple-gel" generator) with spontaneous moisture absorption cycle prepared in Example 1 of the present invention and a cotton strip ("polypyrrole-purple cotton" generator) with asymmetric structural color prepared in Comparative Example 3 measured at the same temperature and humidity. It can be found from the figure that: although the "polypyrrole-purple cotton" generator has a faster power generation speed and a faster growth rate, its voltage is not high due to its limited moisture absorption capacity, while the "purple-gel" generator has a relatively slow power generation speed, but a higher voltage output.
[0068] Figure 7 This is a tensile performance diagram of a hydrodynamic super-tough asymmetric structural color generator device with spontaneous moisture absorption cycle prepared in Example 1 of the present invention. It can be seen from the figure that the generator of the present application has a high tensile capacity and can be applied to more scenarios and service life.
[0069] Table 1 below reflects the maximum V value and the continuous stable time period that can be achieved in Example 1 and each comparative example at the same humidity and temperature.
[0070] Table 1 Test results of Example 1 and Comparative Examples
[0071] It can be clearly seen from the above table that the power generation device prepared in Example 1 has significant advantages over the comparative example, which is mainly reflected in two aspects: 1. High output voltage: The power generation device of Example 1 exhibits a higher output voltage. This result shows that the power generation device using the Py mixed liquid as the conductive liquid can effectively convert the moisture energy in the environment into electrical energy with high conversion efficiency. High output voltage is very beneficial for directly driving electronic devices or storing in batteries because it reduces the loss of energy conversion and improves the overall energy utilization efficiency.
[0072] 2. Long continuous stability time: The power generation device of Example 1 not only has a high output voltage, but also can maintain this high performance stable operation time for a longer time. This means that the device has good long-term stability and reliability, which is crucial for continuous power supply in practical applications. The long-term stable operation capability ensures that the power generation device can continuously provide electrical energy to meet the needs of long-term work, especially in situations where continuous power supply is required.
[0073] These advantages make the power generation device of Example 1 more attractive in practical applications, especially in situations where high-efficiency, high-stability energy solutions are required. High output voltage and long-term stability are two key indicators for evaluating the performance of power generation devices, and Example 1 performs well in both aspects, demonstrating its potential and application prospects in wet gas power generation technology. The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited to this. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. An asymmetric structural color generator device, characterized in that: It comprises a hygroscopic dry gel layer and an asymmetric structural color layer adhered to the hygroscopic dry gel layer; the asymmetric structural color layer comprises a black conductive material active layer and a colored structural color layer partially covering the surface of the black conductive material active layer; the hygroscopic dry gel layer is adhered to the black conductive material active layer.
2. The asymmetric structural color generator device according to claim 1, characterized in that: The area of the colored structural color layer is 1 / 3-2 / 3 of the area of the black conductive material active layer.
3. The asymmetric structural color generator device according to claim 1, characterized in that: The black conductive material active layer is a fabric layer containing polypyrrole.
4. A method for preparing an asymmetric structural color generator device according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. dispersing the gel material, the conductive material, the hygroscopic material, the initiator, and the cross-linking agent into water, heating the reaction, and then freeze-drying to obtain a hygroscopic dry gel layer; S2. The fabric is immersed in a pyrrole mixture containing a dopant, and then a ferric chloride solution is added to perform a polymerization reaction to obtain an active layer of a black conductive material; S3. Using DA-Tris solution and polyvinyl pyrrolidone solution, a colored structural color layer is attached to one side of the active layer of the black conductive material to obtain an asymmetric structural color layer; S4. Bonding the side of the asymmetric structural color layer to which the colored structural color layer is not attached to the hygroscopic dry gel layer by means of an adhesive to obtain the asymmetric structural color generator device.
5. The method for preparing the asymmetric structural color generator device according to claim 4, characterized in that: In step S1, the gel material includes one or more of chitosan, polyacrylic acid, polyethylene glycol, and polyacrylamide; the conductive material includes one or more of pyrrole, carbon nanopowder, graphene, carbon nanotubes, Mxene, and nanocarbon black; the hygroscopic material includes lithium chloride; the initiator includes one or more of potassium persulfate, hydrogen peroxide, and tert-butyl hydroperoxide; and the cross-linking agent includes NN dimethyl acrylamide.
6. The method for preparing the asymmetric structural color generator device according to claim 4, characterized in that: In step S1, the heating reaction temperature is 65-75°C and the time is 1.5-3h.
7. The method for preparing an asymmetric structural color generator device according to claim 4, characterized in that: In step S2, the pyrrole mixture containing dopants includes a mixture of surfactants, organic protonic acids, and pyrrole; the fabric includes one or more of silk fabric, cotton fabric, and linen fabric; the polymerization reaction temperature is 0-5°C and the reaction time is 2-4h.
8. The method for preparing an asymmetric structural color generator device according to claim 4, characterized in that: The specific operation of step S3 is: immersing the active layer of the black conductive material partially in the DA-Tris solution, allowing it to stand to form a colored structural color film, then adding polyvinyl pyrrolidone to terminate the reaction, and removing the unreacted DA-Tris solution to allow the colored structural color film to settle and attach unilaterally to the surface of the immersed black conductive material active layer, thereby obtaining an asymmetric structural color layer.
9. The method for preparing the asymmetric structural color generator device according to claim 8, characterized in that: In step S3, the DA-Tris solution includes 10-20 mmol / L dopamine hydrochloride, 20-30 mmol / L tromethamine, 2-5 mmol / L copper chloride, and 25-35 mmol / L hydrogen peroxide. The pH value of the DA-Tris solution is 8.5-9. The standing time is 6-24 hours.
10. Application of an asymmetric structural color generator device obtained by the preparation method according to any one of claims 4 to 8 in the field of hydrovoltaic power generation.